Dendronized Multifunctional Amphiphilic Polymers as Efficient Nanocarriers for Biomedical Applications. Issue 2 (14th November 2014) - Kumari, Meena; Gupta, Shilpi; Achazi, Katharina; Böttcher, Christoph; Khandare, Jayant; Sharma, Sunil K.; Haag, Rainer; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> To gain insight into the factors that affect stability and transport efficiency under dilution conditions, dendronized and hyperbranched multifunctional amphiphilic polymers are synthesized by following the "grafting to" approach using varied amounts of propargylated alkyl chain with perfect and hyperbranched polyglycerol dendrons on the base copolymer of PEG (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh372v5zgn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯n</alternatives>: 1000 g mol−1) diethylester and 2‐azidopropane‐1, 3‐diol following the "bio‐catalytic method" and "click approach". The dendronized and hyperbranched polymeric systems form supramolecular aggregates and exhibit an efficient transport potential for the model dye "Nile red" in the low μm range in the core–shell‐type architecture provided with distinct amphiphilicity as required for encapsulation. Cytotoxicity studies show the polymeric systems to be non‐toxic over a wide concentration range. The cellular internalization of Nile‐red‐encapsulated supramolecular micellar structures is also studied using cellular fluorescence microscopy and fluorescence‐activated cell sorting (FACS) measurements. A comparison of the data for the dendronized polymers (PEG <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh372v5zf3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />M¯n</alternatives>: 600/1000 g mol−1) with the respective low‐molecular‐weight amphiphile reveal that these polymeric systems are excellent nanotransporters. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>